2001
DOI: 10.1093/ije/30.4.809
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and lung cancer risk in Canada

Abstract: A statistically significant association between income adequacy, education social class and lung cancer risk was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
2
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 29 publications
10
62
2
6
Order By: Relevance
“…This study showed a general inverse relationship between SES and lung cancer incidence risk for all population groups, and a larger gradient exists in males. This result was consistent with the findings of several previous studies (Mao et al 2001;van Loon et al 1995). To explain the socioeconomic disparities in the lung cancer risk, further study is needed, such as the exploration of occupational differences between males and females in Georgia.…”
Section: Sensitivity Analysissupporting
confidence: 91%
“…This study showed a general inverse relationship between SES and lung cancer incidence risk for all population groups, and a larger gradient exists in males. This result was consistent with the findings of several previous studies (Mao et al 2001;van Loon et al 1995). To explain the socioeconomic disparities in the lung cancer risk, further study is needed, such as the exploration of occupational differences between males and females in Georgia.…”
Section: Sensitivity Analysissupporting
confidence: 91%
“…9,10 This study has also shown an inverse relationship between socioeconomic status and lung cancer, contrary to what has been observed in studies from developed countries. 11 Nevertheless, the findings presented in this paper are supported by the fact that in Mexico the prevalence and intensity of tobacco smoking is higher as income or educational level rises. 12,13 Regarding passive smoking, this study finds an odds ratio close to two, very similar to that found in other studies conducted in different parts of the world.…”
Section: Discussionsupporting
confidence: 54%
“…Among women, the socioeconomic gradient in risk tends to be negative (i.e., poorer women are more affected than richer ones) for lung, stomach, esophagus, and cervical cancer, whereas a positive association (richer women are more affected than poorer ones) has been observed for skin melanoma and cancers of the colon, breast, and ovaries (1). A variety of measures of SES have been applied in different studies, but the associations seem to be relatively consistent in Western countries with income (2-9), socioeconomic group (8,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and level of education (2-4, 7-10, 19-21). Several of these studies are large ecological or record linkage studies that have given convincing evidence of the associations between SES and cancer risk, but their lack of individual information on exposures impairs an examination of underlying causal factors related to SES in cancer causation.…”
Section: Introductionmentioning
confidence: 99%
“…One case-control study has investigated the effect of tobacco and alcohol consumption (known carcinogens) on 35 cancer sites (4), whereas another case-control study has considered the role of physical activity (potentially cancer preventive) on 15 sites (15). Other casecontrol studies have been able to control for several potential confounders in the analyses of selected cancers (7,8,22). However, prospective studies addressing the effect of SES on cancer risk are scarce.…”
Section: Introductionmentioning
confidence: 99%